Targeting voter registration with incentives: A randomized controlled trial of a lottery in a London borough. (December 2015) - John, Peter; MacDonald, Elizabeth; Sanders, Michael
Abstract: Does an incentive—in the form of a lottery—increase voter registration, particularly among poorer members of society? In the summer of 2012, two groups of 20, 000 randomly selected households from a London Borough were informed that they would be placed into a prize draw if they registered to vote by 28 September 2012. One group was offered £5000 and the other £1000 while the remaining households in the borough received the standard letter with the same deadline but no lottery offer. The registration rates after the deadline were 46.2 per cent in the £1000 group and 46.6 per cent in the £5000 group compared to 44.7 in the control. Levels of registration in the two treatment groups are statistically different to the control, but not from each other. Households in poorer locations are more receptive of the lottery offer whereas there is no effect in places where richer households live. After the face-to-face canvass of all remaining non-registered households, which took place after the experiment, there were no statistically significant differences between the treatment groups and the control. The study builds on the work of Raja and Schaffner (2012) and Panagopoulos (2013) by finding that incentives work in different ways depending on their level and who is targeted. Highlights: Tests whether a lottery increases voter registration, particularly among poorer members of society. Two groups of 20, 000 randomly-selected households were placed into a prize draw respectively of £5000 or £1000. The registration rates were 46.2 per cent in the £1000 group and 46.6 per cent in the £5000 group compared to 44.7 in the control. Households in poorer locations are more receptive of the lottery offer. After the face-to-face canvass there were no statistical differences between the treatment groups and the control.